FEATURES OF STRATEGIC DEVELOPMENT MANAGEMENT OF PRE-INVESTIGATIVE INVESTIGATION BODIES - GIULMAGOMEDOV, DENYS (Herald of Khmelnytskyi National University. Economic sciences, 2021)
At the present stage of development, organizations play a leading role in society. Organizations are multifaceted and widely represented in various forms, such as enterprises, non-profit organizations, public authorities, associations of citizens or communities, international legal, economic, social institutions, police or security agencies, scientific societies, and so on.Most organizations today operate in a competitive environment that requires them to constantly develop and improve. The winner is the one who acts prudently and effectively. In this aspect, the strategic management of the organization's development is critical to its existence in a competitive environment in the long run.The article substantiates the difference between the dynamics of organizational development of pre-trial investigation bodies from business organizations due to the lack of competition as the main determinant of such development. A comparative analysis of the definitions of strategy, strategic management and organizational development is presented in order to identify the specifics of strategic management of organizational development. Through a systematic analysis of regulations that define the main tasks of pre-trial investigation bodies, the strategic goals of such bodies are identified, which should be taken into account when developing their development strategy. On the basis of the presented material the author's definition of the concept of strategic management of development of bodies of pre-judicial investigation is offered.Based on the analysis, the European Foundation for Quality Management and 7s McKinsey's contemporary evaluation models identify the main trends in organizational development, which in the future should be taken into account by pre-trial investigation bodies when developing their own development strategies. Conclusions are made about the prospects of further research in this direction.
Keywords: strategy; development; organizational development; strategic management of organizational development; pre-trial investigation bodies; law enforcement agencies